Studi Komparatif Komposit Berpenguat Serat Agel yang Diberi Perlakuan Kimia Menggunakan Pembebanan Lentur - Asana, I Wayan Padma Yogi; Widantha, Komang Widhi; Baiti, Risa Nurin (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Natural fiber composites are increasingly explored as sustainable alternatives to synthetic fiber composites because of their renewable character, lower environmental impact, and potential for biodegradable applications. However, the hydrophilic nature of natural fibers often causes poor adhesion with polymer matrices and reduces mechanical performance. This study investigated the effect of NaOH and citric acid surface treatments on Agel fiber-reinforced composites fabricated by the hand layup method, with flexural bending strength as the main response. Three composite groups were prepared, untreated Agel fiber, NaOH-treated Agel fiber, and citric acid-treated Agel fiber. The specimens were cut and tested in bending, and the results were analyzed using normality testing, equal variance testing, one-way ANOVA, and Tukey pairwise comparison.The average flexural bending strengths of the untreated, citric acid-treated, and NaOH-treated composites were 36.922 MPa, 37.784 MPa, and 40.611 MPa, respectively. The statistical assumptions for parametric analysis were satisfied, with the data in each group showing normal distribution and equal variance confirmed. One-way ANOVA indicated a significant difference among the three groups (F = 7.24, p = 0.005). Tukey pairwise comparison showed that the NaOH-treated composite was significantly different from both the untreated composite (p = 0.005) and the citric acid-treated composite (p = 0.031), while the difference between untreated and citric acid-treated composites was not significant (p = 0.678).These results indicate that NaOH treatment is more effective than citric acid treatment in improving the flexural performance of Agel fiber composites under the conditions used in this study. The improvement is attributed to better fiber to matrix interfacial bonding caused by surface modification of the fiber. This study supports the potential of Agel fiber as a sustainable reinforcement material for composite applications.